Minutes of 8th technical and progress monitoring (TPM) meeting of BRACU new campus (session II) - Brac University (Brac University, 2023)
Minutes of the 8th Technical and Progress Monitoring (TPM) meeting (session lI) of BRACU new campus, held on 5th January, 2018..